Parenting and Cortisol in Infancy Interactively Predict Conduct Problems and Callous–Unemotional Behaviors in Childhood. Issue 1 (24th July 2017) - Wagner, Nicholas J.; Mills‐Koonce, W. Roger; Willoughby, Michael T.; Cox, Martha J.
Abstract : This study examines observed maternal sensitivity, harsh‐intrusion, and mental‐state talk in infancy as predictors of conduct problems (CP) and callous–unemotional (CU) behaviors in middle childhood, as well as the extent to which infants' resting cortisol and cortisol reactivity moderate these associations. Using data from the Family Life Project ( n  = 1, 292), results indicate that maternal sensitivity at 6 months predicts fewer CP at first grade, but only for infants who demonstrate high levels of cortisol reactivity. Maternal harsh intrusion predicts fewer empathic–prosocial behaviors, a component of CU behaviors, but only for infants who demonstrate high resting cortisol. Findings are discussed in the context of diathesis–stress and differential susceptibility models.